Thermal analysis on a novel natural convection flat plate collector with perforated tilted transparent insulation material parallel slats (TIM-PS) in Mediterranean climate - Marwa Ammar; Nahed Soussi; Ameni Mokni; Hatem Mhiri; Philippe Bournot (Energy Reports, 2023)
The purpose of this research is the evaluation of heat transfer by natural convection in an innovative flat plate solar collector operating in natural convection mode. The design consists of inclined, perforated slats of transparent insulation material installed between the absorber and the glass cover. Hourly climatic data on the four specific days of solstices and equinoxes was used to investigate the behavior of the novel collector design in the city of Monastir; Tunisia. A comprehensive process, ANSYS FLUENT, was implemented to properly evaluate the thermal performance of the collector. In order to obtain accurate thermal properties of the smart collector façade unit containing the TIM-PS to exploit in the simulation, a validated three-dimensional finite volume model developed using the CFD software was used to solve the conductive, convective and radiative heat transfer properties of the system. We have explored in depth the effect of optical characteristics of the TIM-PS on the collector performance. Present research focuses on the analysis of thermal efficiency profile of flat plate collector with innovative façade in comparison with conventional collector for different climatic conditions. The analysis indicated that innovative façade collector’s efficiency is highly influenced by solar intensity. It was found that TIM-PS façade can effectively reduce the convective heat losses through the front of collector. The simulation results show that perforated tilted TIM-PS offer better performance than conventional façade of collector during all the seasons of the year. Simulations performed for one year predict that with careful selection of the parallel slats properties, the new façade system can generate an efficiency up to 83% in June, 76% in September, 53% in March and 42% in December. The results of the thermal evaluation of this research will help guide the future development of this system, as we have demonstrated that the innovative façade collector can be used all year round. In conclusion, the TIM-PS have great potential and a very wide range of applications in the field of flat plate solar collector.